Exploring the effect of mesopore size reduction on the column performance of silica-based open tubular capillary columns - Hara, Takeshi; Futagami, Shunta; De Malsche, Wim; Baron, Gino V.; Desmet, Gert (Journal of Chromatography A, 2018)
•Layer thickness in PLOT columns can be tuned, independently of HT conditions.•Reduction of mesopore size increases specific surface area, as physically expected.•Reducing mesopore size enhances phase ratio while keeping column efficiency.•Golay-Aris theory can support the experimental data on PLOT columns. We report on a modification in the hydrothermal treatment process of monolithic silica layers used in porous-layered open tubular (PLOT) columns. Lowering the temperature from the customary 95 °C to 80 °C, the size of the mesopores reduced by approximately about 35% from 12−13.5 nm to 7.5−9 nm, while the specific pore volume essentially remains unaltered. This led to an increase of the specific surface area (SA) of about 40%, quasi-independent of the porous layer thickness. The increased surface area provided a corresponding increase in retention, somewhat more (48%) than expected based on the increase in SA for the thin layer columns, and somewhat less than expected (34%) for the thick layer columns. The recipes were applied in 5 μm i.d.-capillaries with a length of 60 cm. Efficiencies under retained conditions amounted up to N = 137,000 for the PLOT column with a layer thickness (df) of 300 nm and to N = 109,000 for the PLOT column with df = 550 nm. Working under conditions of similar retention, the narrow pore/high SA columns produced with the new 80 °C recipe generated the same number of theoretical plates as the wide pore size/low SA columns produced with the 95 °C recipe. This shows the 80 °C-hydrothermal treatment process allows for an increase in the phase ratio of the PLOT columns without affecting their intrinsic mass transfer properties and separation kinetics. This is further corroborated by the fact that the plate height curves generated with the new and former recipe can both be well-fitted with the Golay-Aris equation without having to change the intra-layer diffusion coefficient.